Electrical and luminescence properties of MEH-PPV vertical organic light-emitting transistors with an ultra-thin aluminum source electrode - Mohd Sarjidan, Mohd Arif; Abd Majid, Wan Haliza (INOE, 2018)
Poly[2-methoxy-5-(2'-ethylhexyloxy)-p-phenylene vinylene] (MEH-PPV) based vertical organic light-emitting transistors (VOLETs) have been fabricated. The VOLETs were constructed with a bulk layer of indium-tin-oxide (ITO) and poly(2,3dihydrothieno-1,4-dioxin)–poly(styrenesulfonate) (PEDOT:PSS) as a drain, organic electroluminescent layer of MEH-PPV, an ultra-thin aluminum (Al) as a source, lithium fluoride (LiF) as dielectric and a thick Al as a gate. Electrical and luminescence properties of the devices were investigated. In such VOLETs, the negative bias on the gate electrode has induced a high current density and brighter luminescence, which corresponding to a strong energy band bending in the MEH-PPV layer. Device physics of the fabricated VOLETs were discussed in detail.